Reciprocal actuation core and modular robotic limbs for flying, swimming and running - Song Li; Fangyuan Liu; Xin Dong; Jinwu Xiang; Daochun Li; Pakpong Chirarattananon; Zhan Tu (Communications Engineering)
Abstract Investigations into animal locomotion across diverse environments have highlighted the universal applicability of adjustable reciprocal motion, offering insights into simplifying actuation systems for multi-modal robots. However, achieving unified and efficient reciprocal motion with environmental adaptability in miniature robotic systems is challenging due to constraints of size, weight, and the need for controlled degree of freedom. Here, we present the UniCore, a miniature unified actuation platform capable of flying, swimming, and running with modular appendages. This platform features bio-inspired motor-spring resonance actuation systems, with a central controller that generates four adjustable reciprocal control signals based on a central pattern generator model. Performance validation demonstrates UniCore’s proficiency in achieving three distinct modes of locomotion, underscoring the effectiveness of reciprocal motion for the locomotion of both animals and machines. All in all, this work demonstrates the potential of a unified reciprocal actuation platform to eliminate morphological and actuation redundancies commonly found in existing multi-modal robots, paving the way for more efficient and versatile miniature robotic systems.